(untitled) (Czech Journal of International Relations, 2024)
Bronislav Geremek: born 1932, studied history at the University of Warsaw. In 1960 he became a doctor of philosophy, He lectured at the Sorbonne in Paris and was director of the Centre of Polish Culture in Paris until 1965. V 1965-1980 he was Director of the Department of Medieval History of the Polish Academy of Sciences. He participated in the in the organisation of the strike movement and in the creation of the independent trade union Solidarity. From June 1989 he is a member of the Sejm. In 1989-1990 he was the chairman of the Civic Parliamentary Club Solidarity. Today he is Chairman of the Foreign Affairs Committee of the Sejm and Chairman of the Deputies’ Club Democratic Union.